Examining a brief measure and observed cutoff scores to identify reward and relief drinking profiles: Psychometric properties and pharmacotherapy response - Votaw, Victoria; Mann, Karl; Kranzler, Henry R.; Roos, Corey R.; Nakovics, Helmut; Witkiewitz, Katie (Drug and alcohol dependence, 2022)
Background - Precision medicine approaches attempt to reduce variability in alcohol use disorder (AUD) outcomes by identifying patient characteristics that predict response to a particular treatment. Recent work has examined the extent to which individuals with AUD may seek alcohol to enhance positive experiences (reward drinking) or relieve negative states (relief drinking) and shown that a high reward/low relief phenotype predicts naltrexone treatment response. Yet, limitations of reward/relief drinking measures may hamper efforts to translate findings to clinical practice. We sought to refine a brief measure of reward/relief drinking and develop cutoff scores to identify reward/relief subgroups that predict pharmacotherapy response. - Methods - The Inventory of Drinking Situations (IDS), used in previous studies to measure reward/relief drinking, was administered to 426 participants (77% male; average age = 45.3) in a clinical trial examining naltrexone and acamprosate. - Results - Item response theory and tests of differential item functioning across sex, age, and alcohol dependence severity were used to create a 10-item measure, titled the Reward and Relief IDS (RR-IDS). Cutoff scores on the RR-IDS for the reward/relief drinking subgroups were identified using latent profile and area under the curve analyses. The cutoff scores demonstrated good construct validity. Individuals in the high reward/low relief subgroup who received naltrexone or acamprosate had a decreased likelihood of heavy drinking (large effect sizes) versus those who received placebo. - Conclusions - The RR-IDS is a practical measure for identifying reward/relief subgroups and predicting pharmacotherapy response. Pending replication of these findings, the RR-IDS could be a critical precision medicine tool for prescribing AUD medications.